“Polish Artist – Artist From Poland?” The Question of National Identity in the Study of Artists from Poland in France at the Turn of the 19th and 20th Centuries: the Example of Simon Mondzain - Bobrowska , Ewa (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English version. Original issue: “Archiwum Emigracji” 2013, no. 2 (19) https://apcz.umk.pl/AE/article/view/AE.2013.020